The Effect of a Multiple‐Schedule Arrangement on Mands of a Child with Autism. (12th August 2015) - Vladescu, Jason C.; Kodak, Tiffany
Abstract : Clinical applications of multiple‐schedule arrangements have generally been used to produce discriminated manding. The present study evaluated the effects of a multiple‐schedule arrangement with rules on the rate of mands for one child diagnosed with autism. We sought to bring the participant's mands under discriminative control of adult behavior that closely matched naturally occurring discriminative stimuli in the participant's home environment. The results showed that discriminated manding emerged and responding continued in the presence of a novel therapist. Copyright © 2015 John Wiley & Sons, Ltd.